Insufficiency of Bone Scintigraphy in Vertebral Lesions of Langerhans Cell Histiocytosis Compared to F-18 Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography and Diagnostic Computed Tomography - Koc, Zehra Pinar; Simsek, Selcuk; Akarsu, Saadet; Balci, Tansel Ansal; Onur, Mehmet Ruhi; Kepenek, Ferat (Galenos Yayincilik, 2015)
Langerhans cell histiocytosis (LCH) is a benign disorder related to the histiocytes which can infiltrate bone tissue. The most effective method for demonstrating severity of this disease is PET/CT and bone scintigraphy might show bone lesions. We present a seventeen year old male patient with disseminated LCH presented with exophtalmos and having multiple vertebral lesions which were identified by F-18 FDG PET/CT scan and diagnostic CT but not in the bone scintigraphy.
Keywords: Histiocytosis; Langerhans-cell; bone; scintigraphy; FDG PET/CT